Handling of Basic Foreign Language Skill Using Al-Qur’an Perspective Audio Lingual Method - Arfiyah Febriani, Nur; Setyawan, Aris (The International Journal of Education Management and Sociology, 2023)
The purpose of this study was to find out how the concept of handling basic foreign language skills with the audio-lingual method from the Qur'an perspective. The method used in this study is qualitative while the interpretation method used in this dissertation is the maudhu'i interpretation method. The conclusion of this study found that the audio-lingual method from the Qur'an perspective is a method that integrates memorizing vocabulary with methods of teaching pronunciation and teaching repetition of words, listening, speaking, reading, writing, and presenting and internalizing Islamic values in foreign language learning. In addition, this study found that there were 3 fundamental treatments using the audio-lingual method from the Qur'an perspective in the language learning process at school, namely handling at the planning, implementation, and evaluation stages which caused the learning process of foreign languages in schools to become systematic and the results to be achieved are more measurable so that, the relevance of the application of the audio-lingual method from the Qur'an perspective in handling basic foreign language skills in schools in terms of effectiveness, this method is one of the most effective methods because this method does not only address basic language skills but it can also build children's intelligence.